Optimal planning of biogas production in a set of batch biodigesters - Barreto, Arthur [UNESP]; Petrovic, Sanja; Soler, Edilaine [UNESP]; Florentino, Helenice [UNESP]; Cherri, Adriana [UNESP] (Elsevier, 2025)
The use of organic wastes from industrial, agro-industrial, and household sources has become an essential strategy for generating renewable and sustainable energy. Organic materials processed in biodigesters offer two major benefits: the production of biogas (a renewable energy source) and the creation of biofertilizers (which can enhance agricultural productivity). These benefits increased the interest from both researchers and industry leaders in finding more efficient ways to manage biomass for energy production. One area that has not been thoroughly explored is the scheduling of biogas production in batch biodigesters to meet fluctuating energy demand over time. Biodigesters typically operate in batches, where the substrate is loaded into the system and left to digest for a set period. However, the timing and amount of substrate to be processed are critical issues as the energy demand may vary, and managing production surpluses or shortages is crucial. In this context, a novel integer linear mathematical model has been proposed to address the biogas production scheduling problem. The model focuses on balancing the biogas demand with the operational constraints of biodigesters, such as their availability and production cycles. Several experimental tests have been conducted to validate the model's effectiveness. These tests varied parameters as the biogas demand type, the length of the planning horizon, and the number of biodigesters with different production cycles.The results demonstrate that the proposed model effectively supports decision-making processes for biogas production planning, contributing to cleaner energy systems and sustainable resource management.
Keywords: Biodigesters; Combinatorial optimization; Mathematical model; Production planning; Biogas production; Energy demands; Optimal planning; Optimisations; Organic wastes; Production cycle; Production Planning; Renewable energies; Sustainable energy